A gestão participativa na perspectiva de usuários, trabalhadores e gestores do colegiado gestor de um hospital filantrópico de Belo Horizonte - MG - Marília Aparecida Rosário Oliveira Santos (2021)
Introduction: The collective character of social participation in the health area guided a health reform that forced the State to be: the main health provider in Brazil; to create a unified national health system, without preconditions for access; to decentralize health service delivery; to promote broad popular participation in the design and implementation of health services. The creation of the Local Health Council has strengthened community participation and materialized social control in the health institution that receives public funds, since it must comply with the legislation, having as functions not only inspection, but also, monitor the level of user and worker satisfaction, as well as the proper use of financial resources allocated to that institution, by the manager. In this context, hospitals needed to shift from classical management with vertical hierarchical organization charts to more participatory management that included new actors in decision-making through collegiate managers. Objective: This research aimed to understand Participatory Management from the perspective of users, workers and managers who make up the Management Collegiate of a Philanthropic Hospital in Belo Horizonte. Methodology: This is a qualitative case study with ten members of the managing board of the managerial segments, workers and users who were interviewed through the technique of semi-structured recorded interviews from June to August 2021. The analysis of qualitative data was performed using the content analysis technique. Results: The results showed that the participation in collegiate managers has been expressed as a fundamental element of belonging in the hospital and in the Unified Health System (SUS). The managing collegiate has also been an opportunity to acquire information of different natures, as this information is shared and disseminated by the collegiate representatives, reinforcing their relations with the organization. Study participants stated that participation is facilitated when the hospital management model focuses on sharing decision-making. Another result emphasized was that the performance of the community/user has been recognized as a fundamental element for institutional processes to approach the needs of users. From the point of view of the difficulties pointed out by the participants, they recognize that despite the importance of collegiate spaces, the lack of knowledge of some about the collegiate actions can be a complicating factor in the perception of the importance of this place. Final considerations: It was noticed that the actors involved in the management collegiate of the hospital under study recognize social participation in the hospital institution as a principle of the SUS and, based on this recognition, value the System for allowing the realization of collective, diverse and more inclusive spaces. Participants pointed out facilitating aspects for their participation and also the hindering aspects, among them the lack of recognition from their peers about participation in the collegiate body. The study recommends that the hospital under study reinforce in its admission processes, employee-hospital integration projects that bring out the history of participation as one of the pillars of health care.